A methodology for measuring the total displacements of structures using a laser–camera system. (10th February 2021) - Nasimi, Roya; Moreu, Fernando
Abstract: Railroad bridge inspection manuals recommend measuring bridge displacements under train crossing events. Traditional displacement measurement methods require humans climbing the infrastructure for sensor installation, which is unsafe. Therefore, bridge inspectors are interested in noncontact methods. The authors of this paper developed a methodology that measures the noncontact, reference‐free total transverse displacement of structures using a laser and a camera. Total displacement refers to both dynamic and pseudostatic components of displacement. The developed method can be implemented with off‐the‐shelf hardware components that are lightweight, and simple enough, so researchers can build their own system and test it in the field. First, the paper presents the methodology and tests it with a 1 degree of freedom (DOF) estimation with neither rotation nor elevation change. Subsequently, authors developed a new algorithm combining both laser and camera under arbitrary 6 DOF motion. The results of this research support noncontact reference‐free total displacement measurements of railroad bridges.